PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP LOYALITAS KARYAWAN PADA PT TOR GANDA PERKEBUNAN KARYA PERDANA (Jurnal Riset Manajemen dan Akuntansi, 2023)
Keeping employees in a company that keeps to working in the company. The study purposed to know how compensatition and career development affect employee loyalty partial and simultaneously in PT Tor Ganda Perkebunan Karya Perdana. The study used as many as 105 employees who worked there. The instrument used in this study is a questionnaire. Hypothetical testing was done using linear regression analysis with SPSS 26. The study explains that there is an effect between compensation and career development simultaneous on employee loyalty. Partial, compensation affects employee loyalty, whereas career development does not not affect employee loyalty.